Ag−Fe 3 O 4 Dimer Colloidal Nanoparticles: Synthesis and Enhancement of Magnetic Properties - Lopes, Gleyguestone (2010)
This paper describes a solution-phase route to prepare Ag-Fe3O4 colloidal dimer nanoparticles (NPs) with a dumbbell-like shape. Results show enhancement of the magnetic anisotropy and large coercivity that are explained through the nonzero orbital moment, morb, and the related strong spin-orbit interaction that can be induced by a lattice distortion of the Fe-O bond lengths. In particular, distortions of the octahedral sites in magnetite result in Fe 3d-O 2p mixing and O 2p to Fe 3d charge transfer which, together with crystal field effects, lifts the electronic degeneracy, leading to a nonzero morb. dc magnetization and ferromagnetic resonance were employed for analyzing the magnetic response of the reference Fe3O4 NPs and Ag-Fe3O4 dimer NPs samples, showing a very good agreement with the structural characterization.